Building and Analyzing an Open Repository of Programming Exercises in Portuguese - Lodi, Vinicius Kuster; Sena, João Pedro M.; Reis, Julio C. S. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
Practical exercises are an important part of learning programming. For Brazilian Portuguese, however, there are few data sets with this availability. This work aims to collect and model a data repository for programming exercises, containing instructions, test cases, and exercise metadata. First, platforms are defined as data sources, and Web Scraping techniques are applied to extract the desired content. From the collection, the data is modeled and made available in a public repository called ProgramExBR. A characterization of the data is also presented, revealing a number of interesting discoveries about the text patterns it contains. We hope that this can be useful in various contexts, be it for supporting teachers and students, for training inference models and generating new exercises, or even for an application of personalized recommendation methods in education.